The effect of prophylactic clipping on delayed bleeding after proximal colonic endoscopic mucosal resection: a multicenter, randomized controlled trial (CLIPPER) - Kemper, Gijs; Turan, Ayla S.; Schreuder, Ramon-Michel; Schrauwen, Ruud W. M.; Hadithi, Muhammed; Didden, Paul; Bastiaansen, Barbara A. J.; van der Spek, Bas W.; Droste, Jochim S. Terhaar sive; Schwartz, Matthijs P.; Hazen, Wouter L.; Straathof, Jan Willem A.; Boonstra, Jurjen J.; Alkhalaf, Alaa; Voogd, Fia J.; Allajar, Daud; de Graaf, Wilmar; Koehestanie, Parweez; Roomer, Robert; de Ridder, Rogier J. J.; Moons, Leon M. G.; Siersema, Peter D.; van Geenen, Erwin J. M.; Dutch EMR Study Group (Endoscopy, 2025)
Background Delayed bleeding is the most common complication after endoscopic mucosal resection (EMR) of large colorectal polyps. Randomized controlled trials in high volume centers have suggested that prophylactic clipping of the resection defect reduces delayed bleeding in patients with a high risk for delayed bleeding. We aimed to evaluate the role of prophylactic clipping in reducing delayed bleeding in patients undergoing EMR for large, proximal, nonpedunculated polyps in daily clinical practice.Methods We performed a randomized controlled trial in 19 Dutch hospitals in patients referred for EMR of laterally spreading and sessile polyps ≥ 20 mm in the proximal colon. Patients were randomly assigned (1:1) into groups receiving or not receiving prophylactic clipping. The primary end point was delayed bleeding, and analyses were performed according to intention-to-treat analysis. The trial was registered at ClinicalTrials.gov (NCT03309683).Results Between May 2018 and December 2021, 356 patients with a median polyp size of 30 mm (interquartile range 25–40) in the proximal colon were randomized (177 to the prophylactic clipping group and 179 to the control group). Delayed bleeding occurred in 16 patients (9.0 %) receiving prophylactic clipping and 11 control patients (6.1 %; P  = 0.30). No deaths were reported. Conclusions Prophylactic clipping did not reduce delayed bleeding in patients undergoing EMR for large laterally spreading and sessile polyps in the proximal colon in daily clinical practice.